A Critique of Patriarchal Oppression of Women in The Yellow Wallpaper: A Feminism Literary Criticism - Fikri, Ahmad Rifat; Ashadi, Ashadi; Triyono, Sulis (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. The research on Charlotte Perkins Gilman’s “The Yellow Wallpaper” (1892) is motivated by the social reality of patriarchal oppression in marriage. This research uses a descriptive qualitative method. The study examines the critique of patriarchal oppression—the state in which societies grant men more power and privilege than women. The figure of John portrays patriarchal oppression as a husband who oppresses the narrator as a wife. The study reveals the effects of patriarchal oppression on the narrator’s life. There is also the narrator’s resistance to patriarchal oppression. This research explains further about patriarchal oppression resistance since previous studies focus on women’s difficulties in a patriarchal systemKeywords: patriarchal oppression, feminism, women, the yellow wallpaper